Data protection and the cloud - are you really managing the risks?. - TICHER, PAUL. ([Place of publication not identified], IT GOVERNANCE LTD, 2018)
With a view to helping managers ask the right questions, Data Protection and the Cloud explains how you can effectively manage the risks associated with the Cloud and meet regulatory requirements.
eBooks on EBSCOhost
Keywords: Data protection; Computer security; Computer Security; Protection de l'information (Informatique); Sécurité informatique; Computer security; Data protection